The Ethnobiology of Wild Foods - Pieroni, Andrea (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The ethnobiology of wild foods has received increasing attention within the scientific arena in recent years, since many traditional foodways around the world are still based on some local wild plant, fungal, and animal ingredients, as well as their food products and culinary preparations. Moreover, wild foods have often been the subject of valorization processes at local and regional levels, with complex outcomes in terms of socio-economic impact. Wild foods around the globe therefore urgently further need to be in-depth documented and evaluated, not only for their biological, chemical, technological, nutritional, and pharmacological aspects, but especially in their social, cultural, and religious significance. This reprint bridges the gap between the biological and social scientific aspects of wild foods.